Support for the Hypothetic Remote Memory Formation via Heterosynaptic LTD-mediated Synaptic Degeneration - Zi-Jian Cai (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
Recently, from the cellular forms of memory in the brain concurrently as both homosynaptic long-term potentiation (LTP) and heterosynaptic long-term depression (LTD), it was hypothesized by Cai a new mechanism for the formation of stable remote memory in the brain as heterosynaptic LTD-mediated irreversible neuronal degeneration. This chapter aims to further support such a hypothesis. It has recently been shown that LTD, including heterosynaptic LTD, proceeded with the intracellular clearance of a low quantity of Ca2+/CaM by calcineurin and expression of immediate early gene product Arc (activity-regulated cytoskeleton-associated protein). In turn, it has been demonstrated that Arc might be involved in neuronal degeneration including synapse elimination in Alzheimer’s disease (AD). Therefore, via Arc, it is herein coupled the heterosynaptic LTD to neuronal degeneration including synapse elimination, supporting this new mechanism for the formation of remote memory. Furthermore, it is suggested by this mechanism that the repeated perception or usage of memory may necessarily be required for the formation of stable remote memory. It is also noted the separate effects of slow wave sleep (SWS) in favoring LTD and protecting AD.